Smoking and alcohol by HPV status in head and neck cancer: a Mendelian randomization study - Thakral, Abhinav; Lee, John Jw; Hou, Tianzhichao; Hueniken, Katrina; Dudding, Tom; Gormley, Mark; Virani, Shama; Olshan, Andrew; Diergaarde, Brenda; Ness, Andrew R; Waterboer, Tim; Smith-Byrne, Karl; et al. (Nature communications, 2024)
HPV-positive and HPV-negative head and neck squamous cell carcinoma (HNSCC) are recognized as distinct entities. There remains uncertainty surrounding the causal effects of smoking and alcohol on the development of these two cancer types. Here we perform multivariable Mendelian randomization (MR) to evaluate the causal effects of smoking and alcohol on the risk of HPV-positive and HPV-negative HNSCC in 3431 cases and 3469 controls. Lifetime smoking exposure, as measured by the Comprehensive Smoking Index (CSI), is associated with increased risk of both HPV-negative HNSCC (OR = 3.03, 95%CI:1.75-5.24, P = 7.00E-05) and HPV-positive HNSCC (OR = 2.73, 95%CI:1.39-5.36, P = 0.003). Drinks Per Week is also linked with increased risk of both HPV-negative HNSCC (OR = 7.72, 95%CI:3.63-16.4, P = 1.00E-07) and HPV-positive HNSCC (OR = 2.66, 95%CI:1.06-6.68, P = 0.038). Smoking and alcohol independently increase the risk of both HPV-positive and HPV-negative HNSCC. These findings have important implications for understanding the modifying risk factors between HNSCC subtypes.
Keywords: Squamous Cell Carcinoma of Head and Neck; Male; dlaždicobuněčné karcinomy hlavy a krku; Risk Factors; infekce papilomavirem; Papillomavirus Infections; mendelovská randomizace; nádory hlavy a krku; Case-Control Studies; Head and Neck Neoplasms; mužské pohlaví; jednonukleotidový polymorfismus; Smoking; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; lidé; ženské pohlaví; studie případů a kontrol; Papillomaviridae; Humans; rizikové faktory; pití alkoholu; Alcohol Drinking; Female; lidé středního věku; kouření; Middle Aged